2014
DOI: 10.1159/000369669
|View full text |Cite
|
Sign up to set email alerts
|

MiR-378 Promotes the Migration of Liver Cancer Cells by Down-Regulating Fus Expression

Abstract: Background: miR-378 regulates osteoblast differentiation and participates in tumor cell self-renewal and chemo-resistance. However, the function of miR-378 in liver cancer cell migration has not been reported to date. Methods: miR-378 expression was examined using real-time quantitative PCR. HepG2 cell migration and liver cell invasion were examined using wound-healing and cell invasion assays. Additionally, HepG2 cell metastasis was analyzed in nude mice. Results: miR-378 over-expression enhances HepG2 cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 31 publications
5
27
0
Order By: Relevance
“…Previous study has shown that FUS-binding sites are rich in GU contents and are highly degenerative, and FUS-binding motifs of GGU, GGUG, GUGGU and CGCGC have been previously reported [30], however, the detailed binding sites of FUS on LATS1/2 are still unclear, which would be solved in our future work. It is interesting to note that miR-378 promotes HCC cells migration by down-regulating FUS expression [17], which suggests the inhibitory roles of FUS in HCC migration and this effect is consistent with our results. And since the stemness of cancer cells could confer chemoresistance [31], and FUS expression has been shown to be correlated with cisplatin chemosensitivity in neuroblastoma cell lines [32], future studies could focus on the effects of FUS on chemotherapeutics sensitivity in HCC cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous study has shown that FUS-binding sites are rich in GU contents and are highly degenerative, and FUS-binding motifs of GGU, GGUG, GUGGU and CGCGC have been previously reported [30], however, the detailed binding sites of FUS on LATS1/2 are still unclear, which would be solved in our future work. It is interesting to note that miR-378 promotes HCC cells migration by down-regulating FUS expression [17], which suggests the inhibitory roles of FUS in HCC migration and this effect is consistent with our results. And since the stemness of cancer cells could confer chemoresistance [31], and FUS expression has been shown to be correlated with cisplatin chemosensitivity in neuroblastoma cell lines [32], future studies could focus on the effects of FUS on chemotherapeutics sensitivity in HCC cells.…”
Section: Discussionsupporting
confidence: 91%
“…And FUS regulates AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) receptor function and FTLD/ALS-associated behaviour via stabilizing GluA1 mRNA [16]. In HCC, miR-378 could promote the migration of HCC cells by down-regulating FUS expression [17], which indicates the inhibitory roles of FUS in HCC progression. However, the expression level, roles and related mechanisms of FUS in HCC progression are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Mature miRNAs derive from a complex process, where a primitive form of miRNA (pri-miR) is transcribed by RNA pol II and cleaved by the ribonuclease DROSHA in the nucleus to originate a precursor miRNA (pre-miR), which is exported to the cytoplasm or the endoplasmic reticulum and undergoes a second cleavage by a RNase III endonuclease, Dicer, to become approximately 22 nucleotides length miRNA duplex [7]. Emerging evidence suggests that miRNAs play critical roles in many cellular processes, including cell growth, invasion, metabolism and differentiation [8][9][10][11]. It was recently revealed that miRNAs have been involved in mediating the osteogenic differentiation of osteoblasts and mesenchymal stem cells (MSCs).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-378 was originally identified as an oncogene promoting VEGF expression in human nasopharyngeal carcinoma, 12 now it has been proved to participate in a variety of biological processes, such as cancer metastasis and differentiation. 1314 MiR-378 was strongly upregulated during adipogenic differentiation and positively regulated adipogenesis. 1517 As for osteogenesis, some studies reported that miR-378 promoted osteogenic differentiation, 8 while other study demonstrated that miR-378 suppressed osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%